Clean agricultural production by solar water disinfection in hydroponic systems using synergistic effects. (August 2022) - Farhadi, Rouhollah; Farrokhi Teimourlou, Rahman; Abbasalizadeh, Majid; Ghosta, Youbert
Graphical abstract: Highlights: A solar collector was presented for disinfection with simultaneous UV and heat. An electronic system was proposed to select the best possible disinfection option. Solar UV dose for inactivating some fungi was obtained 136.775 kJ/m 2 . Abstract: Disinfecting and reusing water is a proper method for decreasing chemical control and water consumption. The sun was selected for disinfection as a free, clean, available, and sustainable source with disinfectant effects. Most solar collectors use heat or ultraviolet separately for disinfection. This research is aimed to simultaneously apply heat and solar ultraviolet radiation to profit synergistic effect by combining vacuum tubes and a flat-plate solar collector. In the first stage, the synergistic effect between solar ultraviolet radiation and water temperature on the viability of hydroponic pathogens was measured. Then, the temperature distribution in the collector reservoir was studied using a computational fluid dynamics (CFD) simulation to survey temperature uniformity. An average collector thermal efficiency of 58.66% was obtained. The simultaneous effect of solar ultraviolet radiation and the temperature of 50 ℃ showed a significant reduction of disinfection time rather than only temperature (fungi 5 to 2 h), and the necessary solar ultraviolet dose for inactivating fungi was determined as 136.775 kJ m −2 . Although the presented solar collector was examined for hydroponic systems, it can be used for other applications such as drinking water disinfection.